Color Stability of Two Bulk-Fill Composite Resins - Ameri, Farhad; AbdoTabrizi, Maryam; Ghasemi, Amir; Najafi, Ahmad; Nakhostin, Afrooz; Norouzi, Hanieh; Raoufinejad, Fatemeh (Journal of Dental School, 2019)
Objective: Bulk-fill composites are a group of composite resins designed for easy and fast filling of large cavities. This study aimed to assess the color stability of bulk-fill composites subjected to xenon radiation and evaluate their color change (ΔE) following polymerization. Methods: In this in vitro experimental study, 30 specimens (4mm in height and 8mm in diameter) were fabricated of x-traFil and Tetric N-Ceram universal color bulk-fill composites and A2 shade of Grandio composite (as control). Bulk-fill composites were placed in the mold in 4mm thickness according to the manufacturers’ instructions. In the control group, composite was applied to the mold in two layers each with 2mm thickness. Tetric and Grandio composites were cured for 20 seconds and x-traFil was cured for 10 seconds with a LED light-curing unit. A total of 15 specimens (five of each composite) were used for each test. For assessment of color change due to polymerization, L*, a* and b* color parameters were measured before and immediately after polymerization and also 30 days after immersion in distilled water in an incubator at 37°C and 70% humidity using a spectroradiometer. For xenon test, the specimens were subjected to color analysis after 48 hours of storage in distilled water. Next, they were subjected to xenon lamp radiation in xenon environment chamber for 122 hours at 22°C and 25% humidity and then the color parameters were measured again. The mean and standard deviation (SD) of all values were calculated. One-way and repeated measures ANOVA were used to compare ΔE and ΔL among the groups. Tukey’s HSD test was used for pairwise comparisons. Results: The value of ΔE immediately after polymerization was the lowest for Grandio (4.91) and the highest for Tetric (9.44). Thirty days after the polymerization, ΔE was the lowest in Grandio (3.07) and the highest in Tetric (9.27); ΔE showed a decreasing trend over time in all specimens. Under xenon light radiation, Grandio showed the lowest (1.50) and Tetric showed the highest ΔE (11.15). Conclusion: Following polymerization and under xenon lamp radiation, ΔE of conventional composite was less than that of bulk-fill composites.